Ureteric Endometriosis: a 39 Years Old Lady Presented with Cyclical Lower Abdominal Pain (Journal of Dhaka Medical College, 2018)
Abstract not availableJ Dhaka Medical College, Vol. 27, No.1, April, 2018, Page 98-101